2014
DOI: 10.3171/2014.4.spine13629
|View full text |Cite
|
Sign up to set email alerts
|

Spinal deformity caused by hyperimmunoglobulin E syndrome

Abstract: Hyperimmunoglobulin E syndrome (HIES) is a rare primary immunodeficiency syndrome characterized by recurrent staphylococcal infections in the skin and lungs, with an incidence of less than one case per million persons. Skeletal and connective tissue abnormalities, such as scoliosis, osteoporosis, pathological fractures, and hyperextensive joints, are other manifestations of HIES. However, only one report documents the use of implants to treat spinal deformity caused by HIES, which was discovered follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…and Freeman et al . found that patients with hyperimmunoglobulin E syndrome had idiopathic scoliosis, because the immune deficiencies could lead to abnormalities in the bones and muscles [ 19 , 20 ]. Thus, CD23 may be related to the scoliosis through immune cell infiltration in bones and muscle.…”
Section: Discussionmentioning
confidence: 99%
“…and Freeman et al . found that patients with hyperimmunoglobulin E syndrome had idiopathic scoliosis, because the immune deficiencies could lead to abnormalities in the bones and muscles [ 19 , 20 ]. Thus, CD23 may be related to the scoliosis through immune cell infiltration in bones and muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in STAT3 knock out mice confirm an important role for STAT3 in bone homeostasis 19 ; however, a recent study did not demonstrate a relationship between BMD, as measured on dual-energy x-ray absorptiometry (DEXA) scan or serum markers of osteoclastic activity, and fracture risk in AD-HIES. 1921 Another new finding is that STAT3 is also involved in the regulation of matrix metalloproteinases (MMP) and plasma levels of MMP8 and MMP9 are elevated, while MMP3 is lower in patients with AD-HIES and may be responsible for impaired tissue remodeling. 22 …”
Section: Hyper-ige Syndromesmentioning
confidence: 99%